Major Bioactive Compounds, Volatile and Sensory Profiles of Coffea canephora Flowers and Infusions for Waste Management in Coffee Production - Juliana DePaula; Sara C. Cunha; Fábio Luiz Partelli; José O. Fernandes; Adriana Farah (Foods)
This study aimed to investigate the content of major bioactive compounds and characterize the volatile and sensory profiles of Coffea canephora flowers and their infusions. Dried flowers from six selected genotypes of C. canephora trees and their infusions were analyzed for bioactive compounds using HPLC–DAD, while volatile organic compounds (VOC) were analyzed using GC–MS. Eight chlorogenic acids (CGA), seven phenolic acids, and the alkaloids caffeine and trigonelline were quantified in all methanolic flower extracts. Total CGA, phenolic acids, caffeine, and trigonelline contents in the methanolic extracts ranged between 342.8 and 1079.4 mg/100 g, 27.1 and 41.0 mg/100 g, 515.6 and 745.9 mg/100 g, and 453.8 and 645.2 mg/100 g, respectively. CGA, caffeine, and trigonelline were well extracted (84%, 91%, and 74%, respectively) when the flowers were infused in hot water. No free phenolic acids were identified in the infusions. Eighty-five VOC were identified in the flowers. Aldehydes, monoterpenes, esters, alcohols, monoterpene alcohols, acids, and ketones prevailed in order of the number of compounds. In the infusions, 38 VOC were accurately identified. Monoterpenes and monoterpene alcohols prevailed. In general, floral, jasmine and orange blossom, herbal, green coffee, woody, and sweet were the most cited sensory attributes for fragrance, aroma, and flavor. Considering the typically weak aroma of C. canephora seeds, the aroma and flavor of the flower’s infusions were surprisingly strong and pleasant, showing great marketing potential.